KONSELING BEHAVIORISTIK TEKNIK SELF MANAGEMENT MENINGKATKAN KEDISIPLINAN BELAJAR SISWA SELAMA PEMBELAJARAN DARING SMKN 1 KUDUS - Devi Septiana Ardani; Susilo Rahardjo; Arista Kiswantoro (Universitas Muria Kudus, 2022)
The objectives of the study: (1) describe the causes of the lack of learning discipline behavior by SMKN 1 Kudus students, (2) Obtain an increase in learning discipline during online learning in SMKN 1 Kudus students after being given behavioristic counseling services with self management techniques. The subjects were two students of SMKN 1 Kudus as students with problems with learning discipline during online learning. Data collection techniques include interviews, observation and documentation. Using qualitative descriptive data analysis. The results of the study prove that the application of behavioristic counseling with self management techniques can improve student learning discipline, learning independence, and learning achievement during online learning for students at SMKN 1 Kudus. Based on the results of this study, guidance and counseling teachers should be able to use it to pay attention and recognize student problems in helping to overcome the low level of student discipline during online learning.